Research progress on traditional Chinese medicine compounds in autoimmune-related skin diseases - Wang, Yuhan; Bu, Pengzhi; Deng, Yu; Zhao, Wenyingzi; Pan, Guangtao (Frontiers in Immunology, 2025)
BackgroundAutoimmune-related skin diseases such as psoriasis, atopic dermatitis (AD), vitiligo, and Sjögren’s syndrome (SjS) are characterized by chronic inflammation, immune dysregulation, and complex pathogenesis. Current therapeutic options are limited by side effects, poor efficacy, and high costs. Traditional Chinese medicine (TCM) compounds have demonstrated promising immunomodulatory, anti-inflammatory, and antioxidant effects, offering a novel alternative for managing these conditions.ObjectiveTo systematically review the pharmacological activities and therapeutic potential of bioactive compounds derived from traditional Chinese medicine in treating autoimmune-related skin diseases.MethodsA comprehensive literature review was conducted, focusing on studies that investigated the efficacy, mechanism, and delivery strategies of TCM-derived compounds. Diseases covered include psoriasis, AD, vitiligo, and SjS. Mechanistic pathways such as JAK/STAT, PI3K/AKT, and NF-κB were evaluated alongside compound-specific delivery systems.ResultsNumerous TCM compounds, including curcumin, resveratrol, baicalein, berberine, ginsenosides, and paeoniflorin, exhibited therapeutic effects in preclinical and clinical models. These effects were mediated through various pathways, including inhibition of pro-inflammatory cytokines, restoration of skin barrier function, and modulation of immune cell balance. Nano-based delivery systems further enhanced the stability and bioavailability of these compounds. The compounds also showed potential in reducing oxidative stress and improving melanocyte survival in vitiligo, or restoring glandular secretion in SjS.ConclusionTCM compounds present a valuable resource for the development of safer and more effective therapies for autoimmune-related skin diseases. Further studies are warranted to clarify their mechanisms, optimize delivery systems, and validate clinical efficacy. These natural compounds represent a promising direction for future dermatological drug discovery.